Answer:
106.68 cm
Step-by-step explanation:
Change ft to inches
3.5 ft * 12 inches / 1 ft = 42 inches
Change inches to cm
42 inches * 2.54 cm/ inch =106.68 cm
Answer:
62.4 cm squared
Step-by-step explanation:
8^2-4^2=48
The square root of 48 is 6.928
7*2.928=48.497
(6.928*4)/2=13.856
48.497+13.856= 62.353 or 62.4
Answer:
ii
Step-by-step explanation:
A c A u B
B c A
Aç n Bc = Ac
What do you need to be explainer
The Triangle Sum Theorem states that the sum of the angles of a triangle equal 180°.
Therefore,
45° + 62° + k = 180
107° + k = 180
k = 73°
The value of k is 73°
Answer:
$82.5
Step-by-step explanation:
$16.50 * 5 = $82.5